2021
DOI: 10.1089/scd.2020.0142
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells in Neuroblastoma: Exploring Crosstalk and Therapeutic Implications

Abstract: Neuroblastoma (NB) is the second most common solid cancer in childhood, accounting for 15% of cancerrelated deaths in children. In high-risk NB patients, the majority suffers from metastasis. Despite intensive multimodal treatment, long-term survival remains <40%. The bone marrow (BM) is among the most common sites of distant metastasis in patients with high-risk NB. In this environment, small populations of tumor cells can persist after treatment (minimal residual disease) and induce relapse. Therapy resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 218 publications
0
35
0
Order By: Relevance
“…BM-infiltrating NB cells do not seem to affect the lymphoid lineage in general [ 66 , 67 ], nor specific lymphocyte subsets, such as the immunosuppressive regulatory T cell, Treg and Tr1 [ 68 ]. No information on the features of BM NK cells is presently available, whereas an interesting lymphoid subset, the invariant NKT (iNKT) cells, has been extensively studied in NB tumors.…”
Section: Bm Cellular Composition In Nbmentioning
confidence: 99%
See 4 more Smart Citations
“…BM-infiltrating NB cells do not seem to affect the lymphoid lineage in general [ 66 , 67 ], nor specific lymphocyte subsets, such as the immunosuppressive regulatory T cell, Treg and Tr1 [ 68 ]. No information on the features of BM NK cells is presently available, whereas an interesting lymphoid subset, the invariant NKT (iNKT) cells, has been extensively studied in NB tumors.…”
Section: Bm Cellular Composition In Nbmentioning
confidence: 99%
“…Only recently, the mesenchymal cells present in the BM environment have become the subject of specific studies. Hochheuser et al found that the presence of BM-infiltrating NB cells is associated with an increased number of MSCs in the BM [ 66 ]. However, the fraction of MSCs expressing CD271, a marker of clonogenicity, was reduced and the MSC ability to differentiate was skewed towards osteoblasts [ 66 ].…”
Section: Bm Cellular Composition In Nbmentioning
confidence: 99%
See 3 more Smart Citations